Analysis of current status and influencing factors of hepatitis E knowledge awareness rate among pregnant women in Jiaxing city, Zhejiang province - Feifei GUO; Xiaofei FU; Yuanhang WANG; Yunpeng QI; Wanling ZHOU; Zelin XIANG (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo understand the awareness of hepatitis E knowledge and its influencing factors among pregnant women in Jiaxing city, Zhejiang province, and to provide evidence for the development of community hepatitis E prevention and control strategies. MethodsUsing random cluster sampling and a self-developed questionnaire, we conducted an anonymous on-site survey among 2 512 pregnant women undergoing physical examinations in 8 city- or county-level maternal and child health hospitals in Jiangxi province in April 2023. A multivariate logistic regression model was used to analyze the awareness of hepatitis E knowledge and its influencing factors among the pregnant women. ResultsOf the 2 495 participants (99.32% of women surveyed) with valid responses, 809 (32.42%) were considered knowledgeable about hepatitis E (correctly answering 7 of 12 hepatitis E knowledge questions). Knowledge of hepatitis E varied significantly among participants with different regions of household registration, weeks of pregnancy, occupations, education levels, and annual household income (P < 0.05 for all). Binary multivariate logistic regression analysis showed that, compared with those with local household registration, pregnant women with non-local household registration were less likely to be aware of hepatitis E knowledge (odds ratio [OR] = 0.552, 95% confidence interval [95%CI]: 0.445 - 0.684); compared with those in early pregnancy, pregnant women in late pregnancy were less likely to be aware of hepatitis E knowledge (OR = 0.598, 95%CI: 0.476 - 0.752); compared with those who were civil servants or worked in public institutions, the participants who were medical personnel were more likely to be aware of hepatitis E knowledge (OR = 4.460, 95%CI: 2.663 - 7.469), while the participants who were workers (OR = 0.643, 95%CI: 0.422 - 0.980) and unemployed/self-employed (OR = 0.578, 95%CI: 0.431 - 0.776) were less likely to be aware of the knowledge; compared to those with a junior college education and below, participants with a bachelor's degree and above were more likely to be aware of hepatitis E knowledge (OR = 2.052, 95%CI: 1.648 - 2.555). ConclusionThe awareness of hepatitis E knowledge among pregnant women in Jiaxing city is low, especially among the pregnant women with non-local household registration, in late pregnancy, with an education level of junior college and below, being workers and and unemployed/self-employed; the results suggest that interventions on publicity of hepatitis E knowledge should be promoted among targeted populations.